Biofilm formation and phenotype microarray analysis of Listeria monocytogenes strains from ready-to-eat food / Nowshin Shyara Sharar - Nowshin Shyara , Sharar (2019)
Listeria monocytogenes is an important foodborne pathogen and the causative agent of human listeriosis. Infection is typically acquired through the ingestion of contaminated foods. Ready-to-eat (RTE) foods are currently very popular due to its instant availability and convenience. The occurrence of L. monocytogenes has been reported in RTE smoked fish, seafood, raw meat, sausages and dairy products. In addition, biofilm produced by L. monocytogenes is a major nuisance in food manufacturing industries. Foodborne L. monocytogenes has been reported to form persistent biofilm structures and withstand the routine disinfection procedure in food processing facilities and eventually cross-contaminate the finished products. L. monocytogenes primarily causes infection in the gastrointestinal tract that results in gastritis, meningitis and meningoencephalitis. Therefore, listeriosis is one of the major foodborne illnesses at present. While previous studies emphasized on the intracellular life cycle of L. monocytogenes, knowledge regarding the substrate utilization and metabolic adaptations of L. monocytogenes in the environment are still scarce. Therefore, the objectives of this study were to investigate the carbon and nitrogen substrate utilization of three Malaysian foodborne L. monocytogenes strains, to determine their biofilm forming ability and lastly to identify and correlate the genes involved in catabolism and biofilm formation. Biolog Inc. Phenotype Microarray (PM) technique was used to analyse the catabolic activity of the foodborne strains in 190 carbon and 380 nitrogen sources. PM analysis showed that the carbon and nitrogen catabolic activity of the studied strains were considerably limited, although they all utilized detergents, such as Tween 40 and Tween 80, which are frequently used as sanitizing agents on various surfaces in meat processing industries. The ability to utilize and grow in different substrates provides fitness advantage in stress conditions. Biofilm forming ability was determined using crystal violet assay in nutrient-rich (LB broth) and nutrient-limited (M9 minimal) media and 15 carbon and 8 nitrogen sources were supplemented with minimal medium. All three strains were strong biofilm producers in LB and minimal media. However, thymidine inhibited the biofilm formation in all strains, thereby suggesting a possible role in biofilm control. The whole genome sequencing data of L. monocytogenes strains was analysed and compared with the reference strain L. monocytogenes EGD-e to identify the related genes using the KEGG pathway mapping tools and confirmed by NCBI Nucleotide BLAST analysis. The genomic analysis identified 136 genes associated with biosynthesis, metabolism and biofilm formation, including the genes responsible for surface attachment (flaA, bapL, motA, degU and inlA) and biofilm initiation (secA, recA and relA). Identification of the genes and regulatory pathways involved in different stages of biofilm formation can be beneficial in minimizing biofilm development in food processing industries.